1992
DOI: 10.1109/14.123447
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in partial discharge measurement capabilities at NIST

Abstract: This report describes three techniques un'der development at the National Institute of Standards and Technology (NIST) to measure the properties of partial discharges (PO). These measurements are useful in providing new insight into the mechanisms that influence

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Essentially all that is required for conditional measurements is an electronic filter that controls the data sent to the MCA so that the only pulses recorded are those that appear under restricted conditions satisfied by previous PD events. This system which is called 'stochastic analyzer', is an extended version of a previously described device [14,17] that was used to obtain data on the stochastic properties of dc corona pulses. In addition to the distributions previously measured, the present version allows measurement of many different phase-restricted distributions needed to characterize the stochastic behavior of ac-generated PD.…”
Section: Real-time Stochastic Analyzermentioning
confidence: 99%
See 1 more Smart Citation
“…Essentially all that is required for conditional measurements is an electronic filter that controls the data sent to the MCA so that the only pulses recorded are those that appear under restricted conditions satisfied by previous PD events. This system which is called 'stochastic analyzer', is an extended version of a previously described device [14,17] that was used to obtain data on the stochastic properties of dc corona pulses. In addition to the distributions previously measured, the present version allows measurement of many different phase-restricted distributions needed to characterize the stochastic behavior of ac-generated PD.…”
Section: Real-time Stochastic Analyzermentioning
confidence: 99%
“…Before one can assess the reliability of signatures based on pulse phase or amplitude distributions, it is essential to understand more about the basic mechanisms that determine the stochastic behavior of PD phenomena under different conditions. It has been shown [13][14][15][16][17][18][19] that pulsating PD is in general a complex stochastic process characterized by significant effects of memory propagation. From measurement of conditional phase-of-occurrence and pulse amplitude distributions it can be shown that the amplitude and phase-of-occurrence of any discharge event depends on the amplitudes and phases-of-occurrence of previous events.…”
Section: Introductionmentioning
confidence: 99%
“…The shape of the observed pulse is determined primarily by h(t) and, provided the amplifier is operated in a linear regime, the pulse amplitude and the area under the measured pulse profile are directly proportional to Q [15].…”
Section: Stricklett Et A1: Observbtion Of Pbrtibl Dischbrge In Hexbnementioning
confidence: 99%
“…Results from the latter investigation have appeared in one archival [12] and two conference papers [13,14]. Three other archival papers covering different aspects of this work have also recently been submitted for publication [15][16][17].…”
Section: Introductionmentioning
confidence: 86%